Restoring of an abandoned farm area with trees and herbaceous resources by fallow deer grazing - Staglianò N.; Argenti G.; Pardini A.; Piemontese S.; Talamucci P. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Abandoning of farm surfaces, once utilized for agricultural activities, causes generally a simplification in natural vegetation and environmental degradation. For these reasons it is necessary to point out new possibilities of land management, in order to reduce such environmental impact. In this paper the possibility of restoring a degraded hilly area in Tuscany (Central Italy) is shown, with the utilization of fallow deer (Dama dama) grazing on a trees-herbaceous association.
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)